The Effects of School Accountability Ratings in California Under ESSA on Student Graduation and College and Career Readiness - Drew Atchison; Kerstin Carlson Le Floch; Umut Özek; Justin Luu; Steven Hurlburt; Andrea Boyle (AERA Open)
Using a regression discontinuity design, we examine the effects on graduation and college and career readiness of two types of school performance designations under ESSA in California: (1) color ratings based on individual performance measures that are highly visible, yet do not carry direct ramifications; and (2) federally-mandated Comprehensive Support and Improvement (CSI) designations based on multiple performance measures that are less visible, but have explicit consequences for designated schools. We find significant positive effects of a red color rating (the lowest performance designation) on the outcome on which the rating was based, yet no significant effect of a CSI designation. Descriptive evidence from a principal survey and interviews with district administrators highlight two potential mechanisms behind the differential effects: (1) the relative clarity of color ratings that rely on a single performance measure; and (2) the visibility of color ratings that may induce a sense of urgency among stakeholders.